Carleman estimate and unique continuation for a structured population model. Issue 3 (3rd March 2016) - Uesaka, Masaaki; Yamamoto, Masahiro
Abstract : We consider a time-dependent structured population model equation and establish a Carleman estimate. We apply the Carleman estimate to prove the unique continuation which means that Cauchy data on any lateral boundary determine the solution uniquely.